A Review of Pharmacology of NCS‐382, a Putative Antagonist of γ‐Hydroxybutyric Acid (GHB) Receptor - Castelli, M. Paola (CNS Drug Rev, 2006)
γ‐Hydroxybutyric acid (GHB), a naturally occurring metabolite of γ‐aminobutyric acid (GABA), has been postulated to act as a specific agonist of GHB receptors and as well as a weak GABA(B) receptor agonist. To date, 6,7,8,9‐tetrahydro‐5‐hydroxy‐5H‐benzo‐cyclohept‐6‐ylideneacetic acid (NCS‐382), a semirigid compound structurally related to GHB, is the only compound reported to be an antagonist of the GHB receptor sites. In this article we review the in vivo and in vitro pharmacological properties of NCS‐382 and its interaction with GHB and GABA(B) receptors. Binding studies have demonstrated that NCS‐382 is a stereoselective ligand for GHB‐binding sites, with both, the high and the low component of population, showing the same distribution of GHB receptors. Indeed, this compound did not display affinity for GABA(A), GABA(B), or any other known receptors, while conflicting data have been reported as to its selective antagonist action at GHB receptor. Only a few studies have shown that NCS‐382 antagonizes GHB‐induced effect, but a re‐evaluation of all data reported in the literature suggests that the antagonistic effect of this compound could be due to an indirect action at GABA(B) receptors. As revealed by several behavioral studies, NCS‐382 fails to antagonize GHB discriminative stimuli, GHB‐induced inhibition of locomotor activity and ataxia or suppression of operant responses. Moreover, it is capable of either eliciting qualitatively similar effects to those of GHB or enhancing some actions of GHB. In addition, the NCS‐382‐sensitive electrophysiological effects of endogenous and exogenous GHB observed in vivo have not been completely replicated in vitro. The only electrophysiological action of GHB antagonized in vitro by NCS‐382 required a previous blockade of GABA(B) receptors. We concluded that NCS‐382 is a good ligand but not a selective antagonist for GHB receptor.